Neoumbilicoplasty with a Superiorly Based Abdominal Skin Flap. Issue 4 (April 2018) - Tessler, Oren; Bourn, Lynn; Khoobehi, Kamran; Walters, Jules; Jansen, David
Abstract : Summary: We propose a neoumbilicoplasty technique that can be applied when the umbilical stalk becomes disrupted during an abdominoplasty. This case used surgical concepts that involved progressive thinning of the flap in a 3-cm radius around the neoumbilicus, with increased thinning toward the neoumbilical position. This was followed with suture tacking of the thinned abdominal flap to create a concavity around the neoumbilicus. A longer "U" shaped incision was created and also sutured down to abdominal wall to recreate an umbilical "floor" with the adjacent skin sutured to the superior-based flap to construct the walls of the neoumbilicus. An aesthetically pleasing umbilicus resulted with high patient satisfaction and a lack of postoperative complications. There were no additional scars extending beyond the umbilical region.